2019
DOI: 10.1002/advs.201900531
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Lateral Heterojunction of Selenium‐Coated Tellurium Nanomaterials toward Highly Efficient Solar Desalination

Abstract: Herein, a core–shell tellurium–selenium (Te–Se) nanomaterial with polymer‐tailed and lateral heterojunction structures is developed as a photothermal absorber in a bionic solar‐evaporation system. It is further revealed that the amorphous Se shell surrounds the crystalline Te core, which not only protects the Te phase from oxidation but also serves as a natural barrier to life entities. The core (Te)–shell (Se) configuration thus exhibits robust stability enhanced by 0.05 eV per Se atom and excellent biocompat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…This combination hinders the accumulation of salt on the surface of the evaporator during the desalination process (Figure 7b). In addition, other foams are also beneficial for efficient salt mitigation of solar thermal desalination, such as melamine resin sponge, [ 96 ] VMP, [ 97 ] 3D graphene foam, [ 98 ] etc., all of which show super water pumping, thus transport large quantities water quickly to avoid salt accumulation on the surface of the device due to excessive salt concentration. At the same time, as a water transport material, aerogel can pump water efficiently due to the large number of interconnected pore structures inside it, which has also attracted widespread attention.…”
Section: Salt Mitigation Strategiesmentioning
confidence: 99%
“…This combination hinders the accumulation of salt on the surface of the evaporator during the desalination process (Figure 7b). In addition, other foams are also beneficial for efficient salt mitigation of solar thermal desalination, such as melamine resin sponge, [ 96 ] VMP, [ 97 ] 3D graphene foam, [ 98 ] etc., all of which show super water pumping, thus transport large quantities water quickly to avoid salt accumulation on the surface of the device due to excessive salt concentration. At the same time, as a water transport material, aerogel can pump water efficiently due to the large number of interconnected pore structures inside it, which has also attracted widespread attention.…”
Section: Salt Mitigation Strategiesmentioning
confidence: 99%
“…[19] This equation can be additionally expressed and broken down as mh fg = Aαq solar -Aq water -Ah(T − T ∞ )-Aεσ(T 4 -T ∞ 4 ), wherein α is the solar absorbance of the solar absorber (a photothermal material), q water is the heat flux (including conduction and radiation) to the underlying water, h is the convection heat transfer coefficient, ε is the emittance of the absorbing surface, σ is the Stefan-Boltzmann constant, T is the temperature of solar absorber, and T∞ is the environmental temperature. [20] Based on this equation, it can be deduced that the pathway to achieve efficient solar to vapor generation is to develop a solar absorber possessing the following characteristics: 1) the solar absorber is capable of efficiently absorbing light across the entire solar spectrum (300-2500 nm); [21][22][23] 2) the solar absorber has a high light to heat conversion efficiency, which promotes the conversion of absorbed solar energy into thermal energy; [24,25] 3) the solar absorber has low thermal conductivity to suppress heat loss, arising from conduction, convection, and radiation; [14,16] 4) the solar absorber has good wettability and possesses a porous structure to enable continuous and efficient water transport and evaporation; 5) the solar absorber is mechanically robust and chemically stable to enable its use for practical applications in harsh hypersaline seawater and continuous irradiation conditions over prolonged periods of time: 6) the solar absorber or solar desalination system is provided with salt-rejection properties to reject excess salts left from long-term evaporation. [26,27] Over the past decade, two predominant categories of photothermal materials for solar absorbers have been heavily investigated, with these two categories of photothermal materials based on different photothermal mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…[131][132][133][134][135][136][137][138] The design of a large number of nanomaterials with heterojunctions at the interface between two different crystalline regions indeed has great effects on the development of advanced materials for versatile applications. [139][140][141][142][143][144][145] For example, Zhou et al [134] in 2015 demonstrated the successful synthesis of ultrathin trigonal Te/Se alloyed nanowires with a tunable composition and bandgap. As is shown in Figure 8a, the wire morphology and uniform size distribution with a mean diameter of ≈10 nm were obtained.…”
Section: Se Alloy and Heterojunctionsmentioning
confidence: 99%